Incorporating sleep medicine content into medical school through neuroscience core curricula. (25th September 2018) - Salas, Rachel Marie E.; Strowd, Roy E.; Ali, Imran; Soni, Madhu; Schneider, Logan; Safdieh, Joseph; Vaughn, Bradley V.; Avidan, Alon Y.; Jeffery, Jane B.; Gamaldo, Charlene E.
Abstract : Objective: To present (1) justification for earmarking sleep medicine education as an essential component of all medical school curricula and (2) various avenues to incorporate sleep medicine exposure into medical school curricula through (primarily) neuroscience and neurology courses. Methods: Per consensus of a team of leading neurology and sleep medicine educators, an evidence-based rationale for including sleep medicine across a 4-year medical school curriculum is presented along with suggested content, available/vetted resources, and formats for delivering sleep medicine education at various points and through various formats. Results: Growing evidence has linked sleep disorders (e.g., sleep-disordered breathing, chronic insufficient sleep) as risk factors for several neurologic disorders. Medical educators in neurology/neuroscience are now strongly advocating for sleep medicine education in the context of neurology/neuroscience pre and post graduate medical education. Sleep medicine education is also a critical component of a proactive strategy to address physician wellness and burnout. The suggested curriculum proposes a sleep educational exposure time of 2–4 hours per year in the form of lectures, flipped-classroom sessions, clinical opportunities, and online educational tools that would result in a 200%–400% increase in the amount of sleep medicine exposure that US medical schools currently provide. The guidelines are accompanied by the recommendation for use of technological education, to facilitate more seamless curricular incorporation. Conclusion: Even in this era with limited flexibility to add content to an already packed medical school curriculum, incorporating sleep medicine exposure into the current medical school curriculum is both justified and feasible.